Deploying next generation multicast-enabled applications : label switched multicast for MPLS VPNs, VPLS, and wholesale Ethernet - Joseph, Vinod (Morgan Kaufmann, 2011)
The growth, scale, and prominence of video applications over the years have placed emphasis on the most scalable and efficient way to deliver multi-play content (voice, video and data) to the end user. Multicast is the most effective and efficient carrier of video applications from a network standpoint. Financial organizations deploy large-scale multicast infrastructures to enable trading and e-commerce. The introduction of 4G and beyond makes this technology even more indispensible since mobile operators need an efficient mechanism to deliver repetitive content to many a handset, and multicast is the answer. This is the first book to distill information on this topic from disparate sources. It is written by one of the early implementers, and is the go-to reference for deploying the Next Generation model. This book proves a real benefit to networking professionals from service providers, enterprises, the vendor community, and anyone else who wants to understand this fast emerging and popular scheme of deployment from a vendor-neutral standpoint. Offers contextualized case studies for illustrating deployment of the Next Generation Multicast technology Provides the background necessary to understand current generation multi-play applications and their service requirements Includes practical tips on various migration options available for moving to the Next Generation framework from the legacy.